1993
DOI: 10.1093/genetics/135.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the protein phosphatase 1 gene at 87B can differentially affect suppression of position-effect variegation and mitosis in Drosophila melanogaster.

Abstract: The suppressor of position effect variegation (PEV) locus Su-var(3)6 maps to 87B5-10. The breakpoints of deficiencies that define this interval have been placed on a 250-kb molecular map of the region. The locus is allelic to the ck19 complementation group previously shown to encode a type 1 serine-threonine protein phosphatase (PP1) catalytic subunit. When introduced into flies by P element-mediated transformation, a 5.8-kb genomic fragment carrying this gene overcomes the suppressor phenotype of Su-var(3)6(0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A S66A/S67A non-phosphorylatable mutant of Mlc-2 [13] does not suppress any flw mutant phenotypes (data not shown). Though PP1α87B is the major isoform overall [2], it might be that PP1β9C is the only or major isoform present in muscles. The flw phenotype might then be due to a reduction in the overall PP1 activity in the muscle, rather than any isoform-specific role of PP1β9C.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A S66A/S67A non-phosphorylatable mutant of Mlc-2 [13] does not suppress any flw mutant phenotypes (data not shown). Though PP1α87B is the major isoform overall [2], it might be that PP1β9C is the only or major isoform present in muscles. The flw phenotype might then be due to a reduction in the overall PP1 activity in the muscle, rather than any isoform-specific role of PP1β9C.…”
mentioning
confidence: 99%
“…We therefore measured the PP1 activity of muscle extracts from various PP1 mutants. The total PP1 activity of larvae homozygous for Pp1-87B 1 (also known as Su-var(3)6 01 [1,2]) is correspondingly reduced to about 20% of that of wild type and that of heterozygotes to about 50% of wild type. We found that the PP1 activity from extracts of larval body wall muscles of these genotypes was reduced by a similar proportion (Table 1), showing that PP1α87B is the major PP1 gene in these muscles.…”
mentioning
confidence: 99%
“…Drosophila melanogaster has four genes encoding isoforms of PP1 (Dombrádi et al, 1990(Dombrádi et al, , 1993. Strong alleles of PP1 87B show PP1 activity reduced to ‫%02ف‬ of wild type in extracts of larvae and adults, indicating that this gene is the major isoform at these stages (Baksa et al, 1993). These mutants have a strong cell cycle phenotype: neuroblasts are delayed in mitosis and show aberrant spindle organization and hypercondensed chromatin.…”
Section: Klp38b and Pp1mentioning
confidence: 99%